Strategic assessment of banana research priorities - CGIAR Research Program on Roots, Tubers and Bananas (2014)
The strategic assessment of research priorities for banana is part of a multi‐crop priority assessment exercise coordinated by the CGIAR Research Program on Roots, Tubers and Bananas (RTB). The aim of the overall study is to generate information that can inform the strategy development and priority‐setting process for RTB research. The study follows a six‐step framework: (1) identification of target domains, (2) a constraints analysis, (3) identification of research options matching key constraints, (4) quantification of model parameters, (5) estimation of research impact, and (6) the communication of findings. The five crops included in the study are bananas, cassava, potatoes, sweetpotatoes, and yams. The assessment emphasizes the needs of poor farmers and other vulnerable groups. The methodology for this assessment has drawn on previous priority‐setting studies, especially those conducted at the International Potato Center (CIP) as described in Fuglie and Thiele (2009).